Lysophosphatidic acid (LPA) signalling in cell migration and cancer invasion: A focussed review and analysis of LPA receptor gene expression on the basis of more than 1700 cancer microarrays. (3rd June 2013) - Willier, Semjon; Butt, Elke; Grunewald, Thomas G. P.
Abstract : Lysophosphatidic acid (LPA) is a signalling molecule promoting cell migration, proliferation and differentiation. This review summarises our knowledge on how LPA shapes cytoskeletal remodelling/architecture and contributes to cancer metastasis. Furthermore, we explore the expression signatures of LPA‐receptors and the LPA‐generating enzymes ATX and LIPI via transcriptome analyses of more than 1700 published microarrays. ABSTRACT: Lysophosphatidic acid (LPA) is a ubiquitously present signalling molecule involved in diverse cellular processes such as cell migration, proliferation and differentiation. LPA acts as an autocrine and/or paracrine signalling molecule via different G‐protein‐coupled LPA receptors (LPARs) that trigger a broad range of intracellular signalling cascades, especially the RHOA pathway. Mounting evidence suggests a crucial role of the LPA/LPAR‐axis in cancer cell metastasis and promising studies are underway to investigate the therapeutic potential of LPAR‐antagonists. This review summarises current knowledge on how LPA promotes cytoskeletal remodelling to enhance the migratory and invasive properties of cells, which may ultimately contribute to cancer metastasis. Furthermore, we provide comprehensive transcriptome analyses of published microarrays of more than 350 normal tissues and more than 1700 malignant tissues to define the expression signatures of LPARs and the LPA‐generating enzymes autotaxin (ATX) and lipase member 1 (LIPI). These analyses demonstrate that ATX is highly expressed in a variety of carcinomas and sarcomas, whereas LIPI is almost exclusively overexpressed in highly aggressive Ewing's sarcomas, which underscores the potential contribution of LPA in metastatic disease. In addition, these analyses show that different cancer entities display distinct expression signatures of LPARs that distinguish them from one another. Finally, we discuss current approaches to specifically target the LPA/LPAR circuits in experimental cancer therapy.